2D cine vs. 3D free-breathing self-navigated whole heart for aortic root measurements in congenital heart disease. (8th February 2021) - Nussbaumer, C; Bouchardy, J; Blanche, C; Piccini, D; Pavon, AG; Hugelshofer, S; Monney, P; Stuber, M; Schwitter, J; Rutz, T
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Cardiac magnetic resonance is considered the method of choice for determination of aortic root diameters in congenital heart disease. Usually, a cross-sectional 2D cine stack is acquired perpendicular to the vessel's axis. However, this method requires a considerable patient collaboration and precise planning of image planes. This study compares a recently introduced free-breathing high-resolution 3D self-navigating whole heart sequence (3D self nav) to the 2D cine technique for determination of aortic root diameters. Methods: Two observers measured on 2D cine and 3D self nav cross-sectional planes of the aortic root (figure A and B), acquired on a 1.5T scanner, cusp-commissure (CuCo) and cusp-cusp (CuCu) enddiastolic diameters (figure B and C). Asymmetry of the aortic root was evaluated by the ratio of the minimal to maximum CuCu diameter. CuCu diameters were compared to transthoracic echocardiographic (TTE) aortic root diameters. Results: 65 exams in 58 patients (mean age 32 ± 15y) were included. 2D cine and 3D self nav spatial resolution was 1.4x4.5-6mm and 1.1³mm, respectively. 3D self nav and CuCu yielded larger diameters than 2D cine and CuCo, respectively (table). Intra- and interobserver variabilities were excellent for both techniques ( bias -0.5 to 1.0 mm). Intra-observer variability of the experienced observer was better for 3D self nav (F-test p < 0.05). Aortic root asymmetry was more pronounced in patients with bicuspid aortic valve (BAV: 0.73 (0.69; 0.78) vs. 0.93 (0.9; 0.96), p < 0.001), which was associated with a larger difference of maximum CuCu to TTE diameters: 5.5 ± 3.3 vs. 3.3 ± 3.8 mm, p = 0.03. Conclusion: Both, the 3D self nav and 2D cine techniques allow reliable determination of aortic root diameters. However, the 3D self nav technique and measurement of the CuCu diameters should be privileged to avoid underestimation of the maximum diameter, particularly in patients with asymmetric aortic roots and/or BAV